Aramid nanofiber-reinforced transparent nanocomposites. (June 2015) - Yang, Ming; Cao, Keqin; Yeom, Bongjun; Thouless, MD; Waas, Anthony; Arruda, Ellen M; Kotov, Nicholas A
Nanoscale polymeric fibers are expected to bring about exceptional mechanical and optical properties in composite materials related to the better integration of different properties between fibers and polymers. The discovery of the first aramid nanofiber dispersion from commercial para-aramid macrofibers similar to Kevlar® developed by DuPont allowed the emergence of an innovative nanoscale building block with great potential for engineering novel high-performance polymer nanocomposites. Here we report the fabrication of aramid nanofiber-reinforced polyacrylic-acid thin films using vacuum-assisted flocculation. We show that the resulting composite has high transparency owing to the nanoscale size of the fibers. The multiple hydrogen bonds available at the interface between the polyacrylic acid and nanofibers result in significant improvement of mechanical properties, with Young's modulus outperforming single-walled carbon nanotube composites. The successful use of ANFs in producing transparent, strong and flexible polymer nanocomposites indicates their great potential as an effective reinforcing agent in optical applications.